2022
DOI: 10.1088/1748-9326/ac97ae
|View full text |Cite
|
Sign up to set email alerts
|

Warmer winters are reducing potential ice roads and port accessibility in the Pan-Arctic

Abstract: Transportation in the Pan-Arctic winter is highly dependent on ice roads, which are affected by surface air temperatures and snow cover. In the context of polar increased warming, there is an urgent need to quantify the uncertainties of ice roads and their contribution to terrestrial transport. We evaluated the spatiotemporal characteristics of potential ice road changes by calculating four indicators: potential ice road area (PIRA), potential ice road days (PIRDs), potential ice road onset date (PIROD), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…Zhang et al [30] used the CMIP6 model to predict changes in Arctic shipping lanes and navigation potential over the next 30 years and found that more time would be saved compared with previous studies of Arctic navigation. Dong et al [31] calculated the values for four indicators, potential ice road area, potential ice road days, potential ice road onset date, and potential ice road end date, from 1979-2017 in the Arctic to assess the contribution of changes in potential ice roads to port accessibility. To summarize, existing studies have analyzed overall Arctic accessibility and neglected the important role of ports in the Arctic transportation network.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [30] used the CMIP6 model to predict changes in Arctic shipping lanes and navigation potential over the next 30 years and found that more time would be saved compared with previous studies of Arctic navigation. Dong et al [31] calculated the values for four indicators, potential ice road area, potential ice road days, potential ice road onset date, and potential ice road end date, from 1979-2017 in the Arctic to assess the contribution of changes in potential ice roads to port accessibility. To summarize, existing studies have analyzed overall Arctic accessibility and neglected the important role of ports in the Arctic transportation network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with the Dijkstra algorithm, the A* algorithm can cope with environmental factors more flexibly and improve the accuracy and feasibility of path planning. [15] 2015-2100 × × × Nam et al [22] 2004-2009 × Dijkstra × Li et al [23] 2018-2019 POLARIS Dijkstra × Chen et al [25] 2021-2050 ATAM × × Chen et al [26] 2021-2050 ATAM × × Melia et al [27] 2015-2100 × Dijkstra × Zhou et al [28] 2011-2016 ATAM Dijkstra × Sibul et al [29] 2019-2020 AIRSS A* algorithm × Dong et al [31] 1979-2017…”
Section: Literature Reviewmentioning
confidence: 99%
“…多个机场受此威胁 [23] 。 其次, 北极变化对运输路线、 运输季节的影响 可归纳为改变路径连通性的时空分布。对于运输 路线, 冰层消融促使东北航道的范围扩大和北移、 西 北航道的新路线开辟 [24] , 但也会连同气温、 降水、 积 雪变化制约冬季道路的通行路线 [25] 并使其适宜区减 小 [26] 。Stephenson 等 [27] 融等北极变化的影响主要为: 水运季节延长 [28][29] 、 日 程 改 变 [21,26] 以 及 冬 季 道 路 季 节 缩 短 [21,26] 。 具体 地, Chen 等 [30] 预计 PC6 级破冰船穿越东北航道的季 节 将 从 2021-2025 年 的 8-10 月 延 长 至 2026-2050 年的 7-12 月; Scheepers 等 [31] 发现春、 秋季流 量增加延长了河流的通航期, 但夏季水位下降会缩 短河流运力处于高值的时期, 进而导致河运安排变 化 [32] ; Gädeke 等 [21] 预计 2021-2050 年北极冰路的适 宜期相比 1971-2000 年缩短 30%。…”
Section: 业规模。该行业的附加值占北极各地区生产总值unclassified
“…目的地、 有更长的出行季节 [52][53] , 并使游轮成为更普 遍的旅游出行方式 [8] 。同时, 为了追寻观赏物种, 栖 息地变化也间接推动出游目的地趋于偏远 [54] ; 积雪减 道新路线 [24,[27][28] , 提高航道的通航率 [28][29] -延长北极航道的通航季节 [28][29][30]42] -延长春季、 秋季的河流通航期 [31] 改变道路的路况(如湿滑结冰、 低能见度、 堵塞封闭)和可达性 [27,33,43] 降低船只被冰围困的风险 [34] 、 低温故障 几率 [37] , 提高航行速度 [27] -提升春季的河流运力(流量增加) [31] -致害影响 损耗道路质量 [17,38] 破坏道路 [39][40] 、 管道 [41] 、 机场 [2,23] 和港口 -限制冬季道路的通行路线 [25] 和覆盖 范围 [26][27]38] -缩短冬季道路的适宜期 [1,21,26] 缩短夏季具有高河流运力的时期 [31] , 改变夏/秋季的河运安排 [32] 增加浮冰风险 [1,2,8] , 降低冬季道路的 可靠性 [2,8] 引起恶劣海况(如风暴、 大浪) [2,8,44] 和航空 安全隐患 [45] 降低夏季的河流运力(水位和流量下降), 形成低水位河运风险 [31] 降低雪地摩托 [25] 和全地形车的运输性能 …”
Section: 水运条件, 间接导致游轮旅游前往更高纬和偏远的unclassified
“…Access to northern forest resources is another important logistical barrier that was presented in Chapter 4. Recent research suggests that the ice road networks in the north are increasingly volatile due to the warming climate (Dong et al, 2022). Interview participants who live in northern First Nation communities agreed, explaining that the ice road season is getting shorter and safe trail access is an increasing concern for community members in the winter.…”
Section: Wood Supply and Accessmentioning
confidence: 98%